Iron regulation of North Atlantic eddy phytoplankton productivity - Browning, Thomas J.; Al-Hashem, Ali A.; Hopwood, Mark J.; Engel, Anja; Belkin, Igor M.; Wakefield, Ewan D.; Fischer, Tim; Achterberg, Eric P. (Geophysical Research Letters, 2021)
Cyclonic ocean eddies drive upwelling of deep waters enhanced in nutrients, which can elevate phytoplankton productivity. At mid‐latitudes in the North Atlantic, satellite images show enhanced chlorophyll‐a associated with eddies. However, surface macronutrient concentrations are often not fully depleted in this region, implying enhanced macronutrient supply is not the primary control. We conducted high resolution sampling through two mid‐latitude Atlantic eddies in late spring, located 800 and 350 km east of the Newfoundland Grand Banks. Waters outside of both eddies had unused residual macronutrients, low dissolved iron, and iron‐stressed phytoplankton. Inside both eddies, plankton biomass was higher and macronutrient concentrations lower. However, full macronutrient drawdown and an absence of iron stress were only present in the eddy nearer the continental shelf. From these two examples, iron supply and proximity to shelf iron sources appear to be important factors regulating productivity and macronutrient utilization in mid‐latitude North Atlantic cyclonic eddies.